Egg Reintroduction Following Oral Food Challenge in Japanese Children - Masumi, Hiroki; Takemura, Yutaka; Arima, Tomoyuki; Yamasaki, Koji; Nagai, Megumi; Inoue, Norihiro; Sugimoto, Keisuke (Frontiers in Allergy, 2021)
Background: Oral food challenge (OFC) is the most reliable method for diagnosing food allergies. However, the scarcity of long-term data on eating habits of people after a negative OFC poses a challenge for provisional medical care. Objective: This study was performed to investigate the percentage of people who could reintroduce eggs into their diet several years after an OFC. Methods: Study participants included 0–6-year-old children with negative results from an OFC using one egg as the food allergen, boiled for 20 min, from January 2012–March 2017, 1–3 years after the OFC. Results: A total of 72 subjects were analyzed, out of which 52 were males (72.2%). The median age (range) was 20 months (16–32.3), and the median age (range) at the first OFC was 15 months (12.8–23.3). Eggs were reintroduced in 62 cases (86.1%), while 10 cases (13.9%) did not undergo any diet change. The adjusted odds ratio (OR, 95% CI), with post-OFC to pre-OFC anxiety ≥0.2, was 9.4 (1.0–86), p = 0.04; OR for allergic symptoms that occurred post-OFC was 2.2 (0.45–11), p = 0.34; OR for initial OFC at an age of ≥15 months was 3.2 (0.54–19), p = 0.2; and OR for the history of anaphylaxis from eggs was 0.17 (0.02–1.5), p = 0.11. Conclusion: Most cases reintroduced eggs after an OFC. However, reintroduction did not occur in some cases, which was associated with greater anxiety among caregivers post-OFC. If the caregiver's anxiety is intense, it is necessary to provide psychological intervention and dietary guidance when reintroducing eggs at home after an OFC and to follow-up outpatient long-term progress.